Structural failures and geohazards caused by mountain tunnel construction in fault zone and its treatment measures: A case study in Shaanxi. (August 2022) - Wang, Yaqiong; Li, Jiaqi; Wang, Zhi-Feng; Chang, Hongtao
Highlights: The structural failures and geohazards caused by the fault zone are introduced in detail. Systematic comprehensive treatment measures are proposed for the failures and geohazards. The mechanism of failures occurrence and the rationality of treatment measures are discussed. A new waterproof and drainage system for highway tunnel is proposed. Abstract: Tunneling in fault zone presents considerable challenges to the engineer, including the unexpected failure of supporting structures and the unpredictable geohazards. This paper provides a case study about the structural failures and treatment measures during the construction of the Shengli tunnel crossing the fault fracture zone. During the fault fracture zone construction, structural failures and geohazards such as large deformation of primary lining, water inflow, and collapse were encountered. Before the collapse, the maximum displacement rate of the surrounding rock was 71.7 mm/d, and the extreme deformation of the lining was characterized by the large vault settlement and asymmetric deformation. Combined with on-site monitoring, laboratory tests, and meteorological investigations, the mechanism of structural failures was analyzed. Rocks with low bearing capacity and strong softening, extremely broken rock mass, and abundant groundwater were the main factors leading to the tunnel structural failures. To reduce the adverse effect of fault fracture zone, a series of comprehensive treatment measures were put forward from the aspects of the treatment of collapse body, advanced support, reinforcement of lining, and adjustment of the construction method. Through the field monitoring data of the processing section, the effectiveness of the adopted countermeasures was verified. Based on the monitoring data and field investigations, the process of failures and the rationality of treatment measures were discussed. These results can provide theoretical and technical experience for future similar projects.